The Emerging Role of Neutrophil Extracellular Traps in Arterial, Venous and Cancer-Associated Thrombosis - Zhou, Yilu; Tao, Weimin; Shen, Fuyi; Du, Weijia; Xu, Zhendong; Liu, Zhiqiang (Frontiers in Cardiovascular Medicine, 2021)
Neutrophils play a vital role in the formation of arterial, venous and cancer-related thrombosis. Recent studies have shown that in a process known as NETosis, neutrophils release proteins and enzymes complexed to DNA fibers, collectively called neutrophil extracellular traps (NETs). Although NETs were originally described as a way for the host to capture and kill bacteria, current knowledge indicates that NETs also play an important role in thrombosis. According to recent studies, the destruction of vascular microenvironmental homeostasis and excessive NET formation lead to pathological thrombosis. In vitro experiments have found that NETs provide skeletal support for platelets, red blood cells and procoagulant molecules to promote thrombosis. The protein components contained in NETs activate the endogenous coagulation pathway to promote thrombosis. Therefore, NETs play an important role in the formation of arterial thrombosis, venous thrombosis and cancer-related thrombosis. This review will systematically summarize and explain the study of NETs in thrombosis in animal models and in vivo experiments to provide new targets for thrombosis prevention and treatment.